Race and birth country are associated with discharge location from hospital: A retrospective cohort study of demographic differences for patients receiving inpatient palliative care. (March 2022) - Isenberg, Sarina R.; Bonares, Michael; Kurahashi, Allison M.; Algu, Kavita; Mahtani, Ramona
Summary: Background: While past studies investigated access to palliative care among marginalized groups, few assessed whether there are differences in clinical process indicators based on demographics among those receiving palliative care. We aimed to: describe demographics among patients receiving inpatient palliative care; and evaluate whether demographic variables are associated with differences in disposition (i.e., discharge location), length of stay (LOS), and timing of inpatient palliative care referral and consultation. Methods: Retrospective cohort study using electronic medical record data to study patients seen by inpatient palliative care at Mount Sinai Hospital in Toronto, Canada between April 2018 to March 2019. Primary outcome was disposition. Secondary outcomes were LOS, time from admission to palliative referral, and time from referral to consultation. We summarized quantitative data descriptively and used fisher exact tests to explore relationships between categorial variables. For continuous outcomes, we ran one-way ANOVA tests. Findings: A total of 187 patients were referred to palliative care and met inclusion criteria. Mean age was 68·8 and 55·6% were female. 46·7% were born in Canada, 58·2% were White and 78·4% preferred English communication. Variables significantly associated with disposition were: birth country ( p  = 0·04), and race/ethnicity ( p  = 0·03). Language (F ratio = 3·6, p  = 0·004) was significantly associated with time from admission to palliative care referral. No variables were associated with LOS or time from referral to consult. Interpretation: Inequalities in disposition, and how long it takes to refer to palliative care may exist. Further studies should focus on understanding the underlying practices that constructed, and maintained these inequalities in care. Funding: This research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors.